Calcium alginate microparticles for rare earth elements preconcentration prior to ICP-MS measurements in fresh water. Issue 35 (22nd August 2018) - Arantes de Carvalho, Gabriel G.; Petri, Denise F. S.; Oliveira, Pedro V.
Abstract : Calcium alginate microparticles were used for the preconcentration of rare earth elements for ICP-MS analysis of fresh waters. Abstract : This work presents a method for the single-stage preconcentration and simultaneous determination of 14 rare earth elements (REEs), La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu, in fresh waters using calcium alginate (CA) microparticles as a substrate for further determination by single quadrupole inductively coupled plasma mass spectrometry (ICP-MS). On-line analyte preconcentration was achieved using a flow-injection system incorporating a column filled with CA microparticles (<180 μm size; 300 mg). The proposed procedure was validated for 100 mL test portions, providing an enrichment factor of 100. The method was applied for the analysis of tap water and river water test samples, and validation was carried out with the analysis of the corresponding test samples spiked with 10 μg kg −1 REEs standard solution (La–Lu), wherein recoveries ranging from 90 to 102% were obtained. Coefficients of variation of REEs determinations were smaller than 4.0% (inter-column reproducibility, n = 3). The limit of detection of the method ranged from 0.01 to 0.03 ng kg −1 (achieved with a 100-fold pre-concentration). The procedure (sample loading, rinsing and elution) takes ca. 30 min per replicate. The proposed approach using CA columns is a reliable and low cost alternative for single-stage REEs preconcentration prior to ICP-MS measurements, and can be recommended for the analysis of river water and tap water samples. CA column re-usability was confirmed up to 50 adsorption–desorption cycles.